Influence of maternal HbA1C on fetal insulin levels - H. T., Yashoda; B., Swetha; G., Manasa (International Journal of Contemporary Pediatrics, 2017)
Background: Gestational diabetes is the most common medical complication during pregnancy. The objective of this study was to study the effect of maternal HbA1C levels on fetal insulin levels. Methods: Study was conducted at KIMS. 57 babies born to eligible diabetic pregnant women aged between19 to 40 years with gestational age between 35 and 42 weeks were recruited. Multiple births, gestational age <34 weeks, steroids given within 24 hours before birth, delay of >20 minutes in cord blood collection, delay of >60 minutes before freezing of plasma were excluded. Maternal investigations (HbA1C) were collected from maternal records. Umbilical cord blood was collected immediately after delivery and insulin levels were measured. Results: In this study, mean cord blood insulin levels were 7.83±3.53 μU/ml, mother’s mean HbA1C levels were 6.47±1.26. Statistically significant association was found between maternal HbA1C levels and fetal insulin levels. (r 0.37; P 0.004). Conclusions: Increased cord blood insulin levels were found in infants of diabetic mothers at birth, more so in large for gestation age babies, suggesting inutero fetal programming and hence strict control of maternal diabetes is recommended to decrease long-term fetal effects.